2020
DOI: 10.1089/thy.2019.0698
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative and Postoperative Risk Stratification of Thyroid Papillary Microcarcinoma: A Comparative Study Between Kuma Criteria and 2015 American Thyroid Association Guidelines Risk Stratification

Abstract: Background: The incidence of micropapillary thyroid carcinoma (mPTC) has increased in the last decade. Active surveillance (AS) has been proposed as an alternative management for low-risk mPTC based on preoperative Kuma criteria. Controversy still exists on how to appropriately manage this group of patients, as some low-risk mPTC may harbor some postoperative features associated with disease recurrence as described in the 2015 American Thyroid Association (ATA) guidelines. Methods: We retrospectively reviewed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
0
5
1
Order By: Relevance
“…Recently, researchers in Mexico compared the risk stratification between the Kuma criteria and the 2015 ATA guidelines. They reported that some patients who met the Kuma criteria required more aggressive management than active monitoring 23 . However, we disagree with the opinion that PTMC has been over‐treated.…”
Section: Discussioncontrasting
confidence: 70%
“…Recently, researchers in Mexico compared the risk stratification between the Kuma criteria and the 2015 ATA guidelines. They reported that some patients who met the Kuma criteria required more aggressive management than active monitoring 23 . However, we disagree with the opinion that PTMC has been over‐treated.…”
Section: Discussioncontrasting
confidence: 70%
“…Patients with ETE have a lower 10‐year survival rate (75.2%) and disease‐specific survival rate (84.2%) 64 . Rafael et al 65 report that patients with PTMC having ETE are more likely to acquire metastatic illnesses (lymph node or distant). Similarly, cN0 PTMC patients with ETE showed a 2.84‐fold increase in the chance of developing hv‐CLNM as compared to those without ETE.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with ETE have a lower 10-year survival rate (75.2%) and disease-specific survival rate (84.2%). 64 Rafael et al 65 66 Additionally, Xue et al 67 suggest that HT is protective against recurrence. However, Yin et al 68 show that HT is independently and positively linked to LNM in female PTMC patients aged <55 years.…”
Section: Discussionmentioning
confidence: 99%
“…As Miyauchi highlighted, low-risk PTMC refers to the absence of high-risk features, such as lymph node metastasis, extrathyroidal extension, FNA biopsy findings suggesting high-grade malignancy, growth progression, and location close to the recurrent laryngeal nerve [ 19 ]. Controversy still exists on how to appropriately manage this group of patients, as some PTMCs classified as low risk at the time of the initial surgery may later be associated with disease recurrence or with other features entailing a more aggressive behavior [ 20 ].…”
Section: ⧉ Introductionmentioning
confidence: 99%